Contemporary Spanish cinema - Jordan, Barry, 1950-; Morgan-Tamosunas, Rikki (Manchester University Press, 2019)
'Contemporary focus, right up to date with material from 1980s and 90s. Wide-ranging analyses of major directors, themes, genres and issues, including historical film, genre cinema, women in film and autonomies' --Back cover.
Made available via: manchesterhive.
Includes index.
Keywords: Motion pictures -- Spain.; Cinéma -- Espagne.; Film, TV and radio.; Film theory and criticism.; PERFORMING ARTS / Film / History & Criticism.; Cine español; Motion pictures; Spain; Films.; Motion pictures -- Spain -- History.; The Arts -- Performing arts -- Film & cinema -- Film history, theory & criticism.; PERFORMING ARTS / Film / History & Criticism; Electronic books; History